2000
DOI: 10.1006/viro.2000.0667
|View full text |Cite
|
Sign up to set email alerts
|

Herpes Simplex Virus Infection Induces Replication of Human Immunodeficiency Virus Type 1

Abstract: Genital herpes has been associated with increased efficiency of the sexual transmission and enhanced replication of human immunodeficiency virus type 1 (HIV-1). In this study we demonstrate that exposure to infectious or heat-inactivated herpes simplex virus (HSV) type 1 or 2 virions increases HIV-1 expression in macrophages at least in part by inducing NF-kappaB activity. Neutralizing antibodies to the HSV glycoprotein gB or gD markedly attenuated these virion-mediated effects on HIV-1 expression in macrophag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
51
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 28 publications
1
51
1
2
Order By: Relevance
“…HSV-2 is believed to be the cause, not the effect, of increased HIV viral load, for several reasons. First, in vitro research shows that HSV gene products, such as infected cell protein (ICP)-0, ICP-4, ICP-27 and Us11, directly upregulate HIV replication (36)(37)(38)(39), and that HSV increases expression of HIV in infected macrophages through stimulation of the nuclear factor-kappa B pathway (40). The release of proinflammatory cytokines from HSV-infected cells could similarly stimulate HIV expression, as has been observed for other herpesviruses (41).…”
Section: Evidence That Hsv-2 Infection May Impact On Hiv Prognosismentioning
confidence: 98%
See 1 more Smart Citation
“…HSV-2 is believed to be the cause, not the effect, of increased HIV viral load, for several reasons. First, in vitro research shows that HSV gene products, such as infected cell protein (ICP)-0, ICP-4, ICP-27 and Us11, directly upregulate HIV replication (36)(37)(38)(39), and that HSV increases expression of HIV in infected macrophages through stimulation of the nuclear factor-kappa B pathway (40). The release of proinflammatory cytokines from HSV-infected cells could similarly stimulate HIV expression, as has been observed for other herpesviruses (41).…”
Section: Evidence That Hsv-2 Infection May Impact On Hiv Prognosismentioning
confidence: 98%
“…In support of this possibility, numerous in vitro experiments have shown that HSV-1 gene products can upregulate HIV expression, as mentioned above (36)(37)(38)(39)(40)60). Indeed, in contrast to the clinical literature on HSV-HIV coinfection, the majority of basic science literature on the molecular mechanisms of HSV-HIV interactions has focused on HSV-1, largely because of a greater availability of HSV-1 laboratory strains and animal models.…”
Section: Hsv-1 Is Similar To Hsv-2mentioning
confidence: 99%
“…Furthermore, infection with EBV may influence the expression of HIV because B cells transformed by EBV have the CD4 receptor to which HIV binds (Klatzmann et al 1984). More recently, studies have suggested that increased susceptibility to HIV by EBV infection may be related to greater expression of CCR5 on CD4 lymphocytes (Moriuchi and Moriuchi 2003;Moriuchi et al 2000;Tassan Din et al 2007). In addition, HIV has been shown to infect and multiply within B cells infected with EBV (Carbonari et al 1989).…”
Section: Stress and Acquisition Of Hivmentioning
confidence: 99%
“…Higher prevalence of drug use, incidence of ischemic heart disease, lower survival after myocardial infarction, heightened risk of hypertension, worse self-reported health, poorer physical functioning, higher number of chronic conditions and sexually transmitted diseases Boardman et al 2001;Brugal et al 2003;Chaix et al 2007;Cohen et al 2000;Cozier et al 2007;Das et al 2005;Espinoza et al 2007;Fleming et al 1997;Monteiro et al 2005;McQuillan et al 2004;Roca et al 1995 Glaser et al 1991;Glaser et al 1994;Herbert and Cohen 1993 Kiecolt- Glaser et al 2002 * ;Klatzmann et al 1984;Lin 1993;Margalith et al 1990;Moriuchi et al 2000;Moriuchi and Moriuchi 2003;Nerurkar et al 1987;Rahman et al 1991;…”
mentioning
confidence: 99%
“…HSV may potentiate HIV acquisition by disrupting or activating epithelial cells, which produce proinflammatory cytokines, and may activate or recruit HIV target cells. Additionally, heat-inactivated HSV particles enhance HIV replication in macrophages in vitro, by activating cellular pathways involving NF-B (24). HSV-infected epithelial cells may release noninfectious viral particles, which, in turn, may enhance HIV replication within macrophages or peripheral blood mononuclear cells (PBMC) (36).…”
mentioning
confidence: 99%